Influence of Internal Stresses in Few-Mode Fiber on the Thermal Characteristics of Regenerated Gratings - Mohd Nazal, Nurul Asha; Lim, Kok Sing; Lee, Yen Sian; Mat Salim, Muhammad Aizi; Ahmad, Harith (SpringerOpen, 2019)
The pre-treatment of few-mode fibers (FMFs) has been successfully done with CO2 laser. The wavelength difference, Δλ between the two resonant wavelengths in the few-mode fiber Bragg grating (FMFBG) varies with temperature increment during the annealing process. The results show that the treated fibers with lower stresses have lower thermal sensitivity in Δλ than that of non-treated fiber. However, the treated fibers produce FMFBGs with better thermal durability and regeneration ratio. It is conceived that the presence of those stresses in the pristine fiber is responsible for the high thermal sensitivity in Δλ. The thermal relaxation of stresses and structural rearrangement during the thermal annealing process are responsible for the degradation of the strength and resilience of the regenerated grating. © 2018, The Author(s).